PENGARUH LAMA PERENDAMAN GIBERELIN (GA3) TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS GAMBAS (Luffa acutangula (L.) Roxb) - Rika Renata Malau (Institute of Computer Science (IOCS), 2020)
This study aims to determine the effect of giberelin immersion (GA3) on the growth and production of luffa (Luffa acutangula (L.) Roxb). This research was conducted in the research field of the Faculty of Agriculture, University of North Sumatra, Medan at a height of ± 25 m above sea level in September to December 2019. This study used a Randomized Group Design consisting of two factors. The first factor was three varieties of gambas Prima F1, Primafera F1, and Anggun F1. The second factor was giberelin immersion length of 200 ppm 60 minutes, 120 minutes (control), and 180 minutes to produce 12 treatment combinations of 4 units each with 3 replications. The results showed that the treatment of several varieties significantly affected plant length, number of leaves, number of primary branches, flowering age, fruit length, fruit diameter, fruit weight, canopy wet weight, root wet weight, and percentage of normal fruit. Soaking time treatment significantly affected plant length, number of leaves, canopy wet weight and root wetweight.